Chlamydia Infection: A Main Role of Nursing Intervention Protocols and Laboratory Diagnosis - Alqahtani, Amjad Ali; ALDHAFEERI, TAHANI HUWAYDI; ALDHAFEERI, MASHAEL HUWAYDI; ALDABASI , BANDAR ABDALRAHMAN; ALMUTAIRI, Ahmad Hamoud; NASSER S, ALMUTAIRI, ABDULALI; Alshammari, Ahmed Mohammed Suliman; ALSHAMMARI , AHMED MITHQAL; ALDHAFEERI , DALAL FAHAD; al- amri, Khazim abdullah ali (Journal of Ecohumanism, 2024)
Background: Chlamydia trachomatis is the most prevalent bacterial sexually transmitted infection (STI) globally, with significant public health implications due to its frequent asymptomatic presentation and potential complications, including pelvic inflammatory disease (PID), infertility, and neonatal infections. Despite effective treatments, barriers to screening, diagnosis, and partner management perpetuate transmission. Aim: This article examines the critical role of nursing interventions and laboratory diagnostics in mitigating the burden of chlamydia infections, emphasizing evidence-based screening, treatment protocols, and patient education strategies. Methods: A comprehensive review of clinical guidelines and literature was conducted, focusing on nursing assessments, diagnostic approaches (notably NAAT testing), medical management (azithromycin/doxycycline), and interdisciplinary care coordination. Results: Key findings highlight: (1) NAAT testing’s superiority (95–99% accuracy) for urogenital and extragenital infections; (2) the efficacy of single-dose azithromycin for uncomplicated cases; (3) the necessity of annual screening for high-risk groups (e.g., women ≤25 years, MSM); and (4) nursing’s pivotal role in patient education, partner notification, and adherence support. Expedited partner therapy (EPT) and follow-up testing at 3 months reduced reinfection rates. Conclusion: Multidisciplinary collaboration—integrating targeted screening, prompt treatment, and nursing-led health promotion—is essential to reduce chlamydia’s sequelae and transmission.